2018
DOI: 10.1371/journal.pmed.1002566
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D with risk of type 2 diabetes: A Mendelian randomisation study in European and Chinese adults

Abstract: BackgroundObservational studies have reported that higher plasma 25-hydroxyvitamin D (25[OH]D) concentrations are associated with lower risks of diabetes, but it is unclear if these associations are causal. The aim of this study was to test the relevance of 25(OH)D for type 2 diabetes using genetically instrumented differences in plasma 25(OH)D concentrations.Methods and findingsData were available on four 25(OH)D single nucleotide polymorphisms (SNPs; n = 82,464), plasma 25(OH)D concentrations (n = 13,565), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
95
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 34 publications
6
95
4
Order By: Relevance
“…Over the past decade, a low blood 25-hydroxyvitamin D level has emerged as a possible risk factor for type 2 diabetes, and vitamin D supplementation has been proposed as a potential intervention to lower diabetes risk. 3,4 The hypothesis that vitamin D status may influence the risk of type 2 diabetes is biologically plausible, because both impaired pancreatic beta-cell function and insulin resistance have been reported with low blood 25-hydroxyvitamin D levels. 5 Observational studies support an association between a low blood 25-hydroxyvitamin D level and the risk of diabetes.…”
mentioning
confidence: 99%
“…Over the past decade, a low blood 25-hydroxyvitamin D level has emerged as a possible risk factor for type 2 diabetes, and vitamin D supplementation has been proposed as a potential intervention to lower diabetes risk. 3,4 The hypothesis that vitamin D status may influence the risk of type 2 diabetes is biologically plausible, because both impaired pancreatic beta-cell function and insulin resistance have been reported with low blood 25-hydroxyvitamin D levels. 5 Observational studies support an association between a low blood 25-hydroxyvitamin D level and the risk of diabetes.…”
mentioning
confidence: 99%
“…Over the last decade, low blood 25-hydroxyvitamin D (25[OH]D) level has emerged as a risk factor for type 2 diabetes, and vitamin D supplementation has been hypothesized as a potential intervention to lower diabetes risk ( 6 , 7 ). Observational studies strongly support an inverse association between blood 25(OH)D level and risk of developing type 2 diabetes in diverse cohorts of variable diabetes risk, especially in persons with prediabetes ( 8 , 9 ).…”
mentioning
confidence: 99%
“…Attempts to increase the interests of general public in consumption of food with higher content of vitamin D (either naturally or as a supplement) is increasing (Spiro and Buttriss, 2014;Tessari and Lante, 2017;Aoe et al, 2017). Lately, an association between vitamin D deficit and risk of DM2 development is being discussed in the literature (Lu et al, 2018). Our findings show that vitamin D supplementation helps to improve several clinical manifestation of DM2 and its complications (Zavorkova et al, 2018;Christiansen et al, 2010).…”
Section: Discussionmentioning
confidence: 56%
“…Effects of glucan in prevention and treatment of obesity and clinical manifestation of DM2 were tested both in experimental and clinical studies (Hajer et al, 2008;Richter et al, 2018a;2018b;Lu et al, 2018). Clinical trials confirmed that glucan supplementation resulted in a decrease of glycemic index and lipid metabolism, particularly cholesterol levels (Lu et al, 2018;Sima et al, 2018). Findings of changes in visceral obesity after glucan treatment, accompanied with decrease of weight and BMI are important (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation